Impact of Individual Risk in Explaining Interest Rate's Divergence in the Euro Area - L'oeillet, Guillaume (DEMO, 2016)
Th is paper explores the unique episode of public debt interest rates' divergence in the Euro area between 2008 and 2012. For the fi rst time in the history of the EMU, member states have been distinguished by investors who applied risk premium across the countries. Despite the common currency, the euro area displays some heterogeneity. Th e ECB succeeded in cutting this process with the Outright Monetary Transactions program announced in August 2012. Based on the recent literature and on an empirical analysis, we demonstrate that specifi c factors are behind the rising interest rates spreads in the euro area. Unsustainable fi scal stances and a deteriorated competitiveness mainly explain the dramatic rise of interest rates and risk premium during the sovereign crisis. (original abstract)
Keywords: Eurozone; Public debt; Financial crisis; State financial crisis; Budgetary policy